A Cooperative Target-centric Formation with Bounded Acceleration. Issue 1 (2016) - Sen, Arijit; Sahoo, Soumya Ranjan; Kothari, Mangal
Abstract: In this paper, we propose a consensus based multi-agent distributive controller to form and maintain a target-centric formation. It is assumed that only a subset of agents has target information and agents are subject to limited accelerations. We show that if there is at least one agent which has complete target information and the corresponding communication graph is weakly connected, then a target-centric formation can be maintained around the target. Lyapunov analysis is done to show the stability of the formation under the proposed control law. The performance of the proposed controller is demonstrated through numerical simulations.